COMPARISON OF EFFICACY BETWEEN EDARAVONE AND RILUZOLE COMBINATION THERAPY FOR PATIENT WITH AMYOTROPHIC LATERAL SCLEROSIS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Budianto, Pepi; Mirawati, Diah Kurnia; B, Benedictus; Tan, Kenneth; Hafizhan, Muhammad; Putra, Stefanus Erdana (MNJ (Malang Neurology Journal), 2025)
Background: Amyotrophic Lateral Sclerosis (ALS) is a fatal neuromuscular disease with a survival period of less than 5 years. Although the past decade has shown a major growth of interest in Edaravone research due to its superior efficacy, a growing number of research done on Riluzole combinations for ALS therapy. Objective: A systematic review is needed to compare the patient outcomes as shown in the ALS functional rating scale (ALSFRS-R) of Edaravone and Riluzole combinations. Methods: This research is a systematic review from PubMed, ProQuest, and Science Direct. The studies included were randomized controlled trials (RCT) and post-hoc analysis of RCT published from 2012 to 2023. This research included 16 studies (11 RCT studies and 5 post-hoc studies of RCT). The studies discussed the patient population, side effects, and ALSFRS-R scores. Results: Edaravone showed better efficacy than Riluzole combination in maintaining ALSFRS-R score with mean difference between Edaravone (MD=2.19, 95% CI: 0.42-3.96, p=0.02) and Riluzole (MD=1.67, 95% CI: -0.19-3.52, p=0.08). The meta-analysis showed heterogeneity in both Edaravone (I2=90%, p<0.00001) and Riluzole (I2=77%, p=0.004) studies. Conclusion: The results conclusively showed that Edaravone was more efficacious than the explored Riluzole combinations so far. Nevertheless, Riluzole-Masitinib showed promising results to be further explored.